MetaPhat: Detecting and Decomposing Multivariate Associations From Univariate Genome-Wide Association Statistics - Lin, Jake; Tabassum, Rubina; Ripatti, Samuli; Pirinen, Matti (Frontiers in Genetics, 2020)
Background Multivariate testing tools that integrate multiple genome-wide association studies (GWAS) have become important as the number of phenotypes gathered from study cohorts and biobanks has increased. While these tools have been shown to boost statistical power considerably over univariate tests, an important remaining challenge is to interpret which traits are driving the multivariate association and which traits are just passengers with minor contributions to the genotype-phenotypes association statistic. Results We introduce MetaPhat, a novel bioinformatics tool to conduct GWAS of multivariate and correlated traits using univariate summary results and to decompose multivariate associations into sets of central traits based on intuitive trace plots that visualize Bayesian Information Criterion (BIC) and P-value statistics of multivariate association models. We validate MetaPhat with Global Lipids Genetics Consortium GWAS results, and we apply MetaPhat to univariate GWAS results for 21 heritable and correlated polyunsaturated lipid species from 2,045 Finnish samples, detecting 7 independent loci associated with a cluster of lipid species. In most cases, we are able to decompose these multivariate associations to only 3-5 central traits out of all 21 traits included in the analyses. We release MetaPhat as an open source tool written in Python with built-in support for multi-processing, quality control, clumping and intuitive visualizations using the R software. Conclusions MetaPhat efficiently decomposes associations between multivariate phenotypes and genetic variants into smaller sets of central traits and improves the interpretation and specificity of genome-phenome associations. MetaPhat is available under the MIT license at: https://sourceforge.net/projects/meta-pheno-association-tracer